The Effect of Project Based Learning Model on Students Learning Outcome of Elementary School - Resty Fauziah; Budi Setiawan (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to reveal the Effect of Project-Based Learning Model on Learning Outcomes in Grade V students of SD Kartika 1-11 Padang Timur. The type of research used is a quantitative approach in the form of Quasi Expansion Design. The population in this study were all fifth grade students of SD Kartika 1-11 Padang Timur with samples of the VE class as experimental class 1 and VB as the control class. Sampling is done by probability sampling technique with a type of proportional stratified random sampling. Data analysis techniques through student learning outcomes tests. The hypothesis is proposed using the t test formula. The results showed that there was the influence of Project-Based Learning Model on Learning Outcomes in the experimental group that took science learning using the Project Based Learning model for the control group students taking science learning using a conventional model with an average learning outcome test in the experimental class at 72.92 pretest and posttest 87.58 and the average learning outcomes test for control class students at pretest 63.13 posttest 71.04.